Media Vivocom Z-Book untuk Meningkatkan Minat serta Hasil Belajar Bahasa Inggris Siswa - Amaliah Amaliah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
The research objectives were to understand the effects of Vivocom Z-book. on the students’ interest and learning outcomes in EFL in the State Junior High School 2 Sidoarjo. One Static Group experimental design was employed to compare 35 ninth graders’ comprehension of narrative texts at SMPN2 Sidoarjo before and after using ViVoComZ-Book. This technique was developed as inspired by the students’ interest in playing on-line games. VivoComZ-Book is an acronym. It stands for Video Scribe, Vocab Puzzle, ComicLife3, Z-Book. Videoscribe sparkol was used to draw the students’ attention, and vocab puzzle was used to improve their vocabulary; comiclife3 was used to improve the students’ comprehension and z-book was used to improve the students’ thinking skills. It was discovered that Vivocom Z-book could improve the students’ interest in EFL from the score 2.16 to 4.53, and the students’ learning outcomes from 71% to 91%.